Analysis of factors affecting prognosis of the visual acuity and baseline risk factors for subretinal fibrosis in neovascular age-related macular degeneration patients - Liu, Shihan; Zheng, Minming; Sun, Huixin; Pan, Chunxing; Li, Danting; Zhou, Xiyuan; Zheng, Zheng (Frontiers in Medicine, 2024)
Background To evaluate factors affecting visual acuity prognosis in patients with neovascular age-related macular degeneration (nAMD) following anti-vascular endothelial growth factor (anti-VEGF) therapy via intravitreal injection and to identify baseline risk factors for subretinal fibrosis (SF). Methods A retrospective study of 64 nAMD eyes treated with intravitreal anti-VEGF treatment over 12 months of follow-up was conducted. Demographic and optical coherence tomography characteristics at baseline were recorded to explore the relevant factors affecting visual acuity outcome. Find baseline risk factors for SF development. The primary baseline measures included OCT qualitative and quantitative indicators, and optical coherence tomography angiography (OCTA) quantitative features. Results BCVA (logMAR) at 12 months was positively correlated with age (r = 0.258, p = 0.040), baseline BCVA (r = 0.749, p < 0.001), central macular thickness (CMT) (r = 0.413, p < 0.001), subretinal hyperreflective material (SHRM) (r = 0.304, p = 0.014), intraretinal fluid (IRF) (r = 0.423, p < 0.001), type 2 macular neovascularization (MNV) (r = 0.272, p = 0.029), and ellipsoidal zone breaks (r = 0.299, p = 0.016), and hyperreflective foci (HF) (r = 0.264, p = 0.035). Eyes with SF had worse baseline BCVA (p < 0.001), greater CMT (p = 0.009), and a higher prevalence of IRF (p = 0.005), type 2 MNV (p = 0.001), SHRM (p = 0.012), and HF (p = 0.028). Logistic binary regression analysis showed that baseline BCVA (logMAR) (OR = 0.02, 95% CI: 0.00–0.45, p = 0.013), HF (OR = 0.11, 95% CI: 0.01–0.95, p = 0.045), and type 2 MNV (OR = 0.08, 95% CI: 0.01–0.88, p = 0.039) were independent risk factors of subretinal fibrosis. As for quantitative OCTA parameters, eyes with subretinal fibrosis had a larger microvascular lesion size (p = 0.003), larger vessels area (p = 0.002), higher number of vessel junctions (p = 0.042) and endpoints (p = 0.024), longer total vessel length (p = 0.005), and lower vessel length density (p = 0.042). Conclusion This study enplores baseline OCT and OCTA characteristics associated with subretinal fibrosis in nAMD patients. This information can help predict the occurrence and progression of subretinal fibrosis, potentially leading to more personalized treatment approaches for nAMD patients.